Desenvolvimento, caracterização e avaliação da eficácia de uma suspensão injetável de itraconazol para tratamento da esporotricose felina. - Yamara Viana Sousa (2022)
Sporotrichosis is a chronic fungal infection caused by species of the genus Sporothrix, with S. brasiliensis and S. schenckii being the most relevant. The infection affects animals and humans, with felines being the main reservoirs and sources of dissemination. Sporotrichosis was listed by the World Health Organization as one of the main neglected tropical diseases for the 2021-2030 decade. Itraconazole (ITZ) is the drug of first choice and treatment, both in animals and humans, is usually done via oral administration of capsules. However, as a result of prolonged and regular treatment, the suspension of the treatment is not uncommon, due to adverse reactions, cost and difficulty of oral administration in cats. Thus, aiming to optimize the treatment of sporotrichosis in felines, the present work aimed to develop, characterize and evaluate the effectiveness of an injectable suspension of ITZ. During this study, it was possible to obtain two suspensions based on ITZ, called GT64 and GT109. The formulations were developed after extensive literature review, selection of the most promising excipients and evaluation of the minimum ITZ solubility. The characterization of the formulations was performed through macro and microscopic analyses, rheological profile, osmolarity, particle size and ITZ content by high performance liquid chromatography (HPLC). Moist heat and gamma radiation sterilization methods were also evaluated. Both formulations appeared as a cloudy suspension, easily resuspendable, with non-Newtonian pseudoplastic behavior. In the GT64 formulation, it was possible to observe the presence of a polymeric ''matrix'' stabilizing the ITZ crystals (D90: 39.6 μm) and the osmolarity was 0.795 ± 0.005 Osm/Kg. In the GT109 formulation, however, it was not possible to observe the presence of a polymeric ''matrix'', the ITZ crystals presented a D90 of 51.35 μm and the formulation presented 1.396 ± 0.009 Osm/Kg. The analytical method developed proved to be suitable for evaluating the impurity profile and ITZ content. In the clinical study, only the GT64 formulation was evaluated, as it presented more promising characteristics. The results obtained so far provided evidence of the formulation's potential to contribute to the treatment of feline sporotrichosis.